Reflexões sobre a prática docente e o ensino de Língua inglesa - Farias Neto, Josenildo (2018)
The advent of the foreign language textbook in public schools has contributed to better results in teaching / learning English. Since the book is selected by the National Textbook Program (PNLD, 2011), therefore, as Curriculum Guidelines for Secondary Education (BRASIL, 2006), this should be in accordance with the prerequisites in a section aimed at the knowledge of foreign languages (BRASIL, 2006), which claims to be worked in foreign languages as the following skills: reading, writing practice and contextualized oral communication. Thus, the present study has as main objective to reflect on my own pedagogical practice in the classroom while teaching English in a third year high school class, in the city Arapiraca/AL. This research is initially based on grammar activities of the first chapter of the book “Take Over 3” (2013). The work is divided into four chapters. The Methodology is of a qualitative nature, BORTONI-RICARDO (2008) with an ethnographic character CHIZZOTTI (1991) and an interpretative paradigm. For the research, it is used as collection instruments: the reflective diaries, study plans and questionnaires. The corpus of analysis is the textbook which was mentioned. The work is anchored in STELLA (2013, 2014) researches for new literacies and training of teachers. BAKHTIN (1981), PENNYCOOK (1999), MOITA-LOPES (2011, 2013). ALMEIDA FILHO (1993) The research provided a reflection on my pedagogical practice regarding grammar, allowing me to know other possibilities of acting as a teacher, going beyond the programmatic content of the book, reflecting and transgressing pre-established contents unrelated to the socio-historical and cultural context of the students.